Integration of Virtual Reality and Haptic Feedback for Realistic Training Simulations - Andhika Bintang Pramadya, Yohanes (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2024)
Training in critical sectors like healthcare and engineering demands high realism, which conventional methods often fail to provide due to significant cost and safety risks. Virtual Reality (VR) offers an immersive solution but suffers from a fundamental limitation: the lack of physical touch. This research addresses this problem by designing, implementing, and evaluating an integrated simulation system combining VR with high-fidelity haptic feedback. The primary objective was to create a realistic training platform and quantitatively measure its effectiveness in enhancing practical skill acquisition. The research applied a Research and Development (R&D) methodology to build a prototype simulation in Unity 3D. A key feature is the decoupled system architecture, which runs a high-frequency haptic loop (at 1000 Hz) independently from the visual loop (at 90 Hz) to ensure stability. A proxy-based force rendering algorithm based on Hooke’s Law (F=k*d) was implemented to simulate realistic material resistance. System effectiveness was validated through a pre-test/post-test control group experiment (N=30). The experimental group using the VR-Haptic system showed a significant improvement in procedural accuracy (p < .05) and a 28% reduction in task completion time compared to the control group. User questionnaires also confirmed a high degree of perceived realism and immersion. This study concludes that an integrated, high-frequency visuo-haptic architecture is an effective and necessary solution for developing next-generation realistic training simulators.